ENSINANDO A HISTÓRIA DE SÃO LUÍS ATRAVÉS DA IGREJA DE SANTO ANTÔNIO - FERREIRA, Elizangela de Sousa (2024)
The present work emerges from the reflection on the numerous problems experienced in the teaching of History, mainly the History of São Luís, by the student and teaching public, regarding the teaching materials and methodologies used to teach classes, making the applicability of the discipline lacking important knowledge about regional history and its appreciation, so its objective is to propose methodologies using the Church of Santo Antônio as a heritage for teaching the history of São Luís. To this end, qualitative research was carried out, with the intention of collecting data on the Church of Santo Antônio and thus make it a study and teaching tool. To develop this research, works by authors and their key concepts were collected, such as History Teaching (Silveira, 2010; Magalhães, 2020; Barros, 2008), Local History Teaching aimed at the formation of historical awareness (Schmidt, 2007), Heritage Education (Horta, 1999) and Memory (Pereira and Oriá, 2012). Initially, a survey was carried out in the Dissertation Bank of the PROFHISTÓRIA program, aimed at History Teaching and studies related to heritage, heritage education, memory and local history. Once this was done, articles, books and the most varied authors were consulted in search of contributions to the preparation of this research. From the introductory classes on the content, it was observed that high school students have little or almost no contact with their regional history, due to some factors, such as the low approach in textbooks and few resources for teachers, and the little evidence in our city of the adoption of Heritage Education as a field of action to raise awareness among the community. These factors also contribute to the lack of local appreciation, the general public's lack of knowledge about historical sources, such as the Church, and its importance in the construction of the city's history, which will be explained during the research. However, it appears that the teaching of the History of São Luís, despite often being seen in the background, has tools for its study and teaching, this is the research proposal, the elaboration of a Pedagogical Guide with classes carried out at from and with the object of study. The use of the Church, with due planning, can no longer be seen solely as a religious place, becoming a facilitating method for teaching, causing greater interest and appreciation for regional history.